Rohdea longianthera (Asparagaceae), a new species from Central Yunnan, China - Hu, Li Juan; Zhang, Gao Cheng; Bi, Ming Hui; Chu, Hong Bo; Feng, Hui Zhe (Phytotaxa, 2024)
Rohdea longianthera is described and illustrated as a new species, which is endemic to Chuxiong, western Yunnan, Southwest China. The new species is closely related to R. longipedunculata, but it is actually distinguishable from the latter by the anthers inserted near apex of tube, 2.5–3 mm long and sharply inflexed incrassate deltoid perianth lobes of which the margins are entire, thick and scarcely imbricate. The phenology, distribution and provisional assessment of conservation status of the new taxon are provided. An identification key to all Rohdea species that occur in Yunnan, China is provided for easy identification.